Erin's Heirs : Irish Bonds of Community - Clark, Dennis, 1927-1993 (Book collections on Project MUSE., 2009)
""They will melt like snowflakes in the sun, "" said one observer of nineteenth-century Irish emigrants to America. Not only did they not melt, they formed one of the most extensive and persistent ethnic subcultures in American history. Dennis Clark now offers an insightful analysis of the social means this group has used to perpetuate its distinctiveness amid the complexity of American urban life. Basing his study on family stories, oral interviews, organizational records, census data, radio scripts, and the recollections of revolutionaries and intellectuals, Clark offers an absorbing panorama.